The Level of the motivation for teaching among teachers of the first cycle of basic education (A Field Study In the city of Lattakia) - بركات, غسان; علي , وفيقة; يونس , هدى (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This study aims to recognize the level of the motivation for teaching among teachers of the first cycle of basic education and to recognize the differences between the averages of the responses the teachers on the questionnaire according to the variable of gender, the scientific qualification, and the number of experience years. To achieve the aim of the study, the researcher developed questionnaire; the motivation for teaching included (5) axis, and she applied it on a sample consists of (156) teachers of the first cycle of basic education in the city of Lattakia. the study introduced a group of recommendations, by depending on the suitable statistic ways and using the approach of synthesis, the study found that the level of the motivation for teaching among teachers of the first cycle of basic education was medium. the results have showed that there are differences between the averages of the responses the teachers on the questionnaire according to the variable of gender, the scientific qualification, and the number of experience years. .